A Methodological Approach to Portfolio Evaluation for Official Development Assistance (ODA) Projects, with Special Reference to Contribution Analysis - Choi, Young-Chool (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is, first, to develop an evaluation model that can be applied to the portfolio evaluation of Official Development Assistance (ODA) projects; and second, to present ODA project evaluation procedures based on case studies for the purposes of applying this evaluation model to ODA portfolio evaluation. The significance of this study is that the new ODA portfolio evaluation model it proposes is presented not merely theoretically, but as an example that evaluators can apply easily. It is thought that, if in the future the portfolio is evaluated by these procedures, more accurate evaluation will be performed than is the case at present. However, this evaluation model has several limitations, and in consequence will need to be continuously improved.